TIPE EUFIMISME DALAM CERITA RAKYAT MINANGKABAU - Rosa, Rusdi Noor (English Department FBS UNP, 2012)
In every culture, there are certain things that are not supposed to be speakable or mentioned directly. A number of words are labeled as frivolous, vulgar, or at least inconsiderate. But in communication, for better maintaining social relationship and exchanging ideas, people have to resort to a kind of language whichÂ is known as euphemism. This study is aimed at finding out types of euphemism used in the stories of Minangkabau folklore. This folklore is written in Indonesian language, but the idea of the stories reflects the social life of Minangkabau society. The data were taken from 19 stories of Minangkabau folklore written by Navis, A. A. The result of this study shows that conscious, positive euphemism is the type of euphemism mostly used in the stories. The result of this study also shows that euphemism is strongly influenced by culture. A particular expression needs to be euphemized in one culture may be a common expression in other cultures which, therefore, does not need to be euphemized.